Pengaruh Penggunaan ChatGPT terhadap Produktivitas dan Gaya Belajar Mahasiswa Sistem Informasi Universitas Dian Nuswantoro Semarang - Ahmad Fatih Mu’Alim; Yanura Ibnu Ahada; Muhammad Babassamasi (Journal of Innovative and Creativity, 2025)
This study aims to determine the extent to which the use of ChatGPT has an impact on student productivity and learning styles in the Information Systems Study Program at Dian Nuswantoro University Semarang. This study used quantitative method by distributing Likert scale questionnaires to 32 participants. Based on the analysis, all items in the instrument were declared valid and reliable. There was a very strong correlation between the use of ChatGPT and learning productivity, as well as a strong relationship with students' learning styles. Regression analysis showed that the use of ChatGPT had a significant influence on both variables. The results of this study indicate that ChatGPT plays an important role in increasing the effectiveness and flexibility of the student learning process. Therefore, the findings are expected to serve as a basis in the development of learning strategies that integrate artificial intelligence in an innovative and responsible manner in the higher education environment.